PENGARUH PENAMBAHAN SERBUK BAMBU TERHADAP KARAKTERISTIK CAMPURAN ASPAL BINDER COURSE (AC-BC) - Dewi, Ratna; Ferdiansyah, Yogie; Pataras, Mirka (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
AC-BC is Laston layer of concrete asphalt which is an intermediate layer with minimun hardness of 5 cm. Laston is a layer of road construction that consist a mixtures of hard asphalt and material thas has continious gradation mixed, spread, and solidified at a certain temperature. This leads to the fack that mixture of laston is more sensitive to the varieties of a mixtures proportion.This studydiscussed about impact of bamboo powder used as an addtional material for the mixture of asphalt as much as 1% and 2%. The mixtures characteristic include value of VIM,VMA,VFA,Stability,Flow and MQ. Variant were made to 3 types : normal , additonal 1% bamboo powder and addtional 2% bamboo powder. The analysis resultsshowed value of testing characteristic of addtional 1& bamboo powder fulfill the requirement as addtional (addictive), material as a complement material gradation especially filler agregat with certain percentage of compostition.